2013 APWG eCrime Researchers Summit 2013
DOI: 10.1109/ecrs.2013.6805777
|View full text |Cite
|
Sign up to set email alerts
|

Phish-Net: Investigating phish clusters using drop email addresses

Abstract: The most common approach to collect users' secret credentials from phishing websites is to email the credentials to criminals' email addresses which we call drop email addresses. We propose a clustering algorithm, which is based on the assumption that if there is a common drop email address found in the phishing kits from two different phishing websites, then these two websites are directly related. Based on obfuscated and plain-text drop email addresses, we produce two types of clusters: one is called phishin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The number of phishing websites that rely on kits (as opposed to custom deployments) is unknown, but previous work by Zawoad et al found 10% of phishing sites active in 2013 left trace evidence of phishing kits [39]. This is a lower bound due to a limited coverage in the detection technique for phishing kits and because miscreants may delete traces of the kit after deployment.…”
Section: Phishing Kitsmentioning
confidence: 86%
See 1 more Smart Citation
“…The number of phishing websites that rely on kits (as opposed to custom deployments) is unknown, but previous work by Zawoad et al found 10% of phishing sites active in 2013 left trace evidence of phishing kits [39]. This is a lower bound due to a limited coverage in the detection technique for phishing kits and because miscreants may delete traces of the kit after deployment.…”
Section: Phishing Kitsmentioning
confidence: 86%
“…The type of information stolen depends on the kits, but prior studies have shown that they harvest a victim's username, password, and geolocation information among other sensitive data [8,19,30,39]. Han et al estimated the success rate of kits by monitoring the activity of real visitors to infected honeypots, of which 9% submitted some data to the phishing page [19].…”
Section: Phishing Kitsmentioning
confidence: 99%
“…Work on phishing profiling was aimed to understand and observe attacker activities to better predict phishing emails [30], while some studies [35], [36] use it as a first step to improve the accuracy of a phishing/benign classifier. Seifollahi et al [37] focused more on the authorship analysis and identifying the cybercriminal groups, while Zawoad et al clustered emails in order to identify phishing attacks generated by off-the-shelf phishing kits [38]. Approaches have also looked at using semi-supervised phishing profiling to predict new spear phishing campaigns [39].…”
Section: B Email Clusteringmentioning
confidence: 99%
“…[17] and [18] use a structural analysis technique comparing local domain files to create clusters of related phish. Zawoad et al cluster phishing websites using email addresses receiving the phished credentials [19]. These email addresses are found in the phishing kits used to create the phishing websites.…”
Section: Related Workmentioning
confidence: 99%